Business and Economics: Metrics and Peer Review in the journal: "WSEAS Transactions on Business and Economics". (June 2020) - Bardis, Nikos; Ekonomou, Lambros; Borne, Pierre; Ntalianis, Klimis; Mercorelli, Paolo; Katehakis, Michael N; Kintzios, Nikos; Bulucea, Cornelia Aida; Planas, Maria Isabella Garcia
Abstract: The Conference MMCTSE 2020 was in collaboration with the Journal "WSEAS Transactions on Business and Economics". In this paper, the Metrics, the Peer Review and some statistical results of this Journal: "WSEAS Transactions on Business and Economics" is outlined.